Filsafat Pendidikan Kristen dari Perspektif Teologi Kristen - Arip Surpi Sitompul; Yohana Nelly P.; Ridwan Junaedi Tinambunan; Rumondang Bellania Sibarani; Dame Munte (Lembaga Pengembangan Kinerja Dosen, 2025)
This article examines the philosophy of Christian education from a theological perspective that emphasizes the integration of faith, knowledge, and divine values as the foundation for shaping the whole person. Christian educational philosophy is understood as a theological reflection encompassing three central dimensions: ontology, epistemology, and axiology. Ontologically, the highest reality is God as the Creator, while humans are understood as His creation, endowed with dignity and spiritual responsibility. Epistemologically, the source of true knowledge originates from God through His revelation, both general and special, so that the learning process must be rooted in a faith-based relationship that leads to divine truth. Axiologically, Christian education is oriented toward forming Christlike character expressed through love, honesty, responsibility, and service to others. This study employs a qualitative approach using a literature review method, analyzing theological and philosophical sources related to the concept of Christian education. The findings reveal that Christian education is theocentric, transformative, and holistic, integrating intellectual, moral, and spiritual aspects within the learning process. A Christian philosophy of education rooted in Scripture is expected to serve as a foundation for addressing modern challenges such as secularization, relativism, and the post-truth era, as well as forming a generation that is faithful, knowledgeable, and Christlike for the glory of God.